Relations of power in early Neo-Assyrian state ideology - Karlsson, Mattias (Studies in ancient Near Eastern records, 2016)
Introduction -- The primary sources of the study -- The relationship between the great gods and the foreign lands -- The relationship between the great gods and the king of Assyria -- The relationship between the king of Assyria and the foreign lands -- Ideological development within the reigns -- Local propaganda and regional politics -- Ideological comparison between the reigns -- The development of Assyrian state ideology -- Conclusion of the study -- Appendices and indices: List of the inscriptions; List of the iconography; Spatial distribution of the major primary sources; Deity hierarchy in the texts; Divine titles and epithets in the texts of Ashurnasirpal II; Divine titles and epithets in the texts of Shalmaneser III; Divine titles and epithets in the texts of the other kings; Royal titles and epithets of Ashurnasirpal II; Royal titles and epithets of Shalmaneser III; Royal titles and epithets of the other kings; List of the most common royal titles and epithets I; List of the most common royal titles and epithets II; Visual representations of Ashurnasirpal II; Visual representations of Shalmaneser III and the other kings; List of the most common royal visual representations; Early Neo-Assyrian state ideology in history